PENGARUH COMPETITIVE ADVANTAGE, PROFITABILITAS DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (Studi pada perusahaan IDX LQ45 yang terdaftar di Bursa Efek Indonesia Tahun 2015-2020) - Romadhani, Ahmad; Saifi, Muhammad; Nuzula, Nila Firdausi (Profit: Jurnal Adminsitrasi Bisnis, 2022)
This study aims to analyze and explain the effect of competitive advantage (cost of capital, capital intensity, advertising expenses), profitability (ROA, ROE, NPM), dividend policy (DPR, DPS, Yield) on firm value (MBR, MBA, Tobin’s Q). The researcher uses explanatory research with a quantitative approach and the object of the research uses the company IDX LQ45 which is listed on the Indonesia Stock Exchange in 2015-2020. The total sample in this study was 4 companies from a population of 45 companies that met the sampling criteria and this study uses Partial Least Squares (PLS) as research data management. The results show that the effect of competitive advantage has a significant effect on profitability, profitability has no significant effect on firm value, competitive advantage has a significant effect on dividend policy, dividend policy has no significant effect on firm value and competitive advantage has a significant effect on firm value